Bidirectional roles of Dhh1 in regulating autophagy. Issue 10 (3rd October 2019) - Liu, Xu; Jin, Meiyan; Yao, Zhiyuan; Bernard, Amélie; Klionsky, Daniel J.
ABSTRACT: Macroautophagy/autophagy activity is carefully modulated to allow cells to adapt to changing environmental conditions and maintain energy homeostasis. This control notably occurs in part through the regulation of autophagy-related ( ATG ) gene expression. Others and we have jointly shown that under nutrient-rich conditions Dhh1 mediates the degradation of certain ATG mRNAs, most significantly that of ATG8, through a Dcp2-dependent decapping pathway to maintain gene expression and autophagy activity at a basal level. More recently, we illustrated that under nitrogen-starvation conditions Dhh1 switches its role to become a positive regulator of autophagy, and promotes the translation of ATG1 and ATG13 mRNAs to meet the increased demand for autophagy activity. This regulation helps selected ATG mRNAs to escape the general repression in translation that occurs when nutrients are limited and TOR is inhibited. Our studies also suggest that Dhh1's nutrient-dependent bidirectional regulation of auto-phagy is conserved in more complex eukaryotes. Abbreviations: ATG: autophagy related; EIF4EBP: EIF4E binding protein; UTR: untranslated region.